Penerapan Pembelajaran Bahasa Inggris yang Menyenangkan - Husna, Ahsanul (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research aims to determine the application of enjoyable English learning. This research is library research that uses a descriptive qualitative approach. Learning English is a type of learning that is a scourge and frightening for many students, because English is considered a difficult lesson and difficult to understand. So many students feel lazy and unenthusiastic when learning English. This situation will of course affect the level of achievement of learning objectives. The quality of learning will decrease and learning objectives will not be achieved. Therefore, a strategy is needed to overcome this problem. Teachers must try to make students feel interested and enthusiastic about learning English. One way to make students feel interested and enthusiastic about learning English is by implementing fun English learning.